The doctrine of human rights in the field of private law relations: legal theoretical aspects - Horielova, Veronica Yu.; Omelchuk, Vasyl A.; Kalinichenko, Oleksandr F.; Naida, Inna V.; Sagaydak, Yuliya V.; Горєлова, Вероніка Юріївна (Rushing Water Publishers Ltd., 2019)
World globalization and transboundary orientation to the best and most efficient provision of human rights today is the driving force behind ensuring the implementation of the human rights doctrine in the civil law of Ukraine. Despite the diversity of approaches to this topic, its complex research has not been conducted that, in turn, has generated the interest of the article’s authors. With consideration of new legal approaches and practice of law enforcement, the authors made the following conclusions: (1) review of doctrinal approaches to determination institute of human rights in the context of today’s realities demonstrated that the one and unified concept of introduction human rights in the civil legislation at both national and international levels is absent; in addition, an efficient mechanism of unification has not been found; (2) analysis of legal foundations of the establishment of human rights institution in the field of legislation revealed their close connection, interdependence, provided an author’s conditional list of approaches to consolidate the human rights doctrine in the national civil law, to outline existing gaps and inaccuracies in legal regulation, and (3) studying concepts of human rights protection in the civil legislation gave an opportunity to state that legal civil protection of legalized in national law of Ukraine human rights is currently in a transformational state under the influence of European integration aspirations of Ukraine and internationally updated standards. However, despite this tendency, competent state institutions are able to provide adequate protection for civil-detailed human rights, in particular by implementing the practice of the European Court of Human Rights in legal proceedings. Conducted research provides grounds to argue that the modern national civil law of Ukraine is a stable basis, and it consolidates various conceptual approaches to the doctrine of human rights. Moreover, this branch is ready for qualitative and effective transformations and improvements on the way to ensuring the substantive unity of doctrine and the law at the national level.
Keywords: Civil law of Ukraine; Doctrine; European Court of Human Rights; Globalization; Human rights; Private law relations